A comprehensive Bayesian reanalysis of the SARAS2 data from the epoch of reionization. Issue 3 (29th April 2022) - Bevins, H T J; de Lera Acedo, E; Fialkov, A; Handley, W J; Singh, S; Subrahmanyan, R; Barkana, R
ABSTRACT: We present a Bayesian re-analysis of the sky-averaged 21-cm experimental data from SARAS2 using nested sampling implemented with polychord, spectrally smooth foreground modelling implemented with maxsmooth, detailed systematic modelling and rapid signal emulation with globalemu . Our analysis differs from previous analysis of the SARAS2 data through the use of a full Bayesian framework and separate modelling of the foreground and non-smooth systematics. We use the most up-to-date signal models, including Lyman-α and CMB heating parametrized by astrophysical parameters such as star formation efficiency, X-ray heating efficiency, minimal virial circular velocity of star forming galaxies, CMB optical depth, and the low energy cutoff of the X-ray spectral energy distribution. We consider models with an excess radio background above the CMB produced via radio emission from early galaxies and parametrized by a radio production efficiency. A non-smooth systematic is identified and modelled as both a frequency damped sinusoid introduced by the electronics and separately from the sky. The latter is modulated by the total efficiency of the antenna and marginally favoured by the data. We consider three different models for the noise in the data. The SARAS2 constraints on individual astrophysical parameters are extremely weak, however, we identify classes of disfavoured signals. We weakly disfavour standard astrophysical models with high Lyman-α fluxes and weak heating and more confidently disfavour exotic models with high Lyman-α fluxes, low X-ray efficiencies, and high radio production efficiencies in early galaxies.